Meningkatkan Perkembangan Kognitif Dalam Mengenal Lambang Bilangan Melalui Permainan Memancing Angka Di Kelas A TK Pertiwi 01 Jetis Kecamatan Jaten Kabupaten Karanganyar Tahun Pelajaran 2022/2023 - Nur'Aini, Yuliana; Yuli Setiawan, M. Hery; Heru Sri Suryanti, Hera (Jurnal AUDI: Jurnal Ilmiah Kajian Ilmu Anak dan Media Informasi PAUD, 2025)
YULIANA NUR'AINI. IMPROVING COGNITIVE DEVELOPMENT IN KNOWLEDGE OF NUMBER SYMBOLS THROUGH NUMBERS FISHING GAMES IN CLASS A TK PERTIWI 01 JETIS DISTRICT JATEN, KARANGANYAR DISTRICT IN ACADEMIC YEAR 2022/2023. Thesis. Surakarta. Faculty of Teacher Training and Education, Slamet Riyadi University, Surakarta. July 2023This study aims to find out how to improve cognitive development in recognizing number symbols through a number fishing game in class A Kindergarten Pertiwi 01 Jetis. This study uses a class action research model from Kemmis & Mc. Taggart, the subjects of this study were 15 students. Data collection methods used are observation, interviews and documentation. The research instrument used observation guides, data analysis techniques used quantitative descriptions, indicators of success were determined, namely if at least 75% of 15 children had an increase in cognitive development in recognizing number symbols through a number fishing game with very good development criteria.The results of the study show that fishing for this number can improve cognitive abilities in class A Kindergarten Pertiwi 01 Jetis. This is evidenced in the achievement of very well developed indicators. In cycle I, the cognitive development of children experienced an increase of 9 out of 15 children or 60% were in the starting to develop category. Whereas in cycle II the cognitive development of children experienced an increase of 14 out of 15 children or 93.3% in the very well developed category and developed according to expectations. The study was stopped until cycle II because it met the success indicator criteria, namely at least 75% of 15 children. This proves that fishing for numbers can improve cognitive development in recognizing number symbols.Keywords: Cognitive Development, Number Symbol, Number Fishing Game